Iron + folic acid distribution and consumption through antenatal care: identifying barriers across countries - Sununtnasuk, Celeste; D'Agostino, Alexis; Fiedler, John L. (Cambridge University Press, 2016)
The prevalence of maternal anaemia remains unacceptably high in developing countries. At the same time, the percentage of women who consume one or more Fe+folic acid (IFA) tablets during pregnancy remains persistently low. The objective of the present study was to identify where, within antenatal care (ANC) programmes, pregnant women falter in obtaining and consuming an ideal minimum of 180 IFA tablets.Data from Demographic and Health Surveys were used to develop a schematic which identifies four sequential ‘falter points’ to consuming 180 IFA tablets: ANC attendance, IFA receipt or purchase, IFA consumption and the number of tablets consumed.Twenty-two countries with high burdens of undernutrition.A sample of 162 958 women, 15 to 49 years of age, with a live birth in the past 5 years.Across all countries, 83 % of all pregnant women had at least one ANC visit, 81 % of whom received IFA tablets. Of those receiving IFA tablets, 95 % consumed at least one. Overall adherence to the ideal supplementation regimen, however, was extremely low: only 8 % consumed 180 or more IFA tablets. There were only two countries in which the percentage of pregnant women consuming 180 or more tablets exceeded 30 %.While most women receive and take some IFA tablets, few receive or take enough. The analysis identifies where ANC-based distribution of IFA falters in each country. It enables policy makers to design and prioritize follow-up activities to more precisely identify barriers, an essential next step to improving IFA distribution through ANC.